Dissemination of government policies regarding micro community activity restrictions to control the rate of Covid-19 - L.M. Azhar Sa'ban; Farid Yusuf Nur Achmad; Muh. Askal Basir; Andi Reni; Siti Sarah; Abdan Syakur (Community Empowerment, 2022)
This community service seeks to offer a thorough knowledge of the risks of Covid-19 dissemination, as well as raise public awareness about the need of following health standards and obeying Micro Community Activity Restrictions (PPKM) for the whole community. The issue is that the outcomes of related policies have not been able to considerably curb Covid-19's spread. The lecture technique is utilized to disseminate the community service material for all members of the Winning Village community. As a consequence of this socialization, the public's knowledge of Covid-19's spread and hazards, as well as public awareness of how to protect themselves while performing regular activities in workplaces, marketplaces, houses of worship, and other places, is increasing.